Competitiveness of Indonesian Tea Export in Southeast Asia Markets - Nursodik, Hendi; Imam Santoso, Siswanto; Nurfadillah, Suryani (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 16 No 1 (2022): Vol.16, No.1, 2022DO - 10.24843/SOCA.2022.v16.i01.p01, 2022)
Tea is a popular export commodity from Indonesia. It has been exported worldwide, especially to Southeast Asia countries. However, the popularity of the tea export market attracts export competitors, which in turn served a strenuous chance to win in the market. The objective of the study was to analyze the competitiveness and factors that affected the exported Indonesian tea in Southeast Asia Market. The data analysis method applied was the Revealed Comparative Advantage (RCA), Trade Specialization Ratio (TSR), and data panel regression (Fixed-Effect Model). Findings showed that exported Indonesian tea had a strong level of comparative competitiveness. Analysis revealed that Indonesia tended to be a tea exporter on the export expansion stage. The real GDP of the countries of destination, exported tea price, the population of the countries of destination, and RCA index had delivered significant influence for the exported volume of Indonesian tea to the Southeast Asia countries.